2019
DOI: 10.1002/ijc.32396
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in BRCA1/2 mutation carriers and noncarriers under prospective intensified surveillance

Abstract: Comparably little is known about breast cancer (BC) risks in women from families tested negative for BRCA1/2 mutations despite an indicative family history, as opposed to BRCA1/2 mutation carriers. We determined the age‐dependent risks of first and contralateral breast cancer (FBC, CBC) both in noncarriers and carriers of BRCA1/2 mutations, who participated in an intensified breast imaging surveillance program. The study was conducted between January 1, 2005, and September 30, 2017, at 12 university centers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
(86 reference statements)
2
20
1
1
Order By: Relevance
“…The 10-year cumulative contralateral breast cancer risk following the initial breast cancer diagnosis was 21.1% for BRCA1, 10.8% for BRCA2 and 5.1% for non-carriers [15]. These findings were confirmed in a recent multicentre study where the 10-year cumulative risk was 25.1% (95% CI 19.6-31.9) for BRCA1, 13.5% (95% CI 9.2-19.1) for BRCA2 and 3.6% (95% CI 2.2-5.7) for non-carriers [16].…”
Section: Brca 1/2 Carriers and Contralateral Breast Cancer Risksupporting
confidence: 67%
“…The 10-year cumulative contralateral breast cancer risk following the initial breast cancer diagnosis was 21.1% for BRCA1, 10.8% for BRCA2 and 5.1% for non-carriers [15]. These findings were confirmed in a recent multicentre study where the 10-year cumulative risk was 25.1% (95% CI 19.6-31.9) for BRCA1, 13.5% (95% CI 9.2-19.1) for BRCA2 and 3.6% (95% CI 2.2-5.7) for non-carriers [16].…”
Section: Brca 1/2 Carriers and Contralateral Breast Cancer Risksupporting
confidence: 67%
“…In the univariate analysis, the age at first diagnosis of BC was significantly associated with the risk of developing CBC in BRCA carriers. 98 In the study conducted by Kyrova et al, the percentage of CBCs was significantly higher in familial cases of carriers versus noncarriers (p=0.02), 46 but other analyses have provided contrasting results. In a retrospective study by Drooger et al enrolling 691 patients with BRCA1/2-associated breast cancer, most of them were younger than 40 years at the time of the first diagnosis, and no association between radiotherapy for the primary BC and the risk of CBC was found in both the global population (HR 0.82, 95% CI 0.45–1.49) and in the subgroup of patients younger than 40 years at first diagnosis (HR 1.36, 95% CI 0.60–3.09).…”
Section: Tsgs Mutations Related Breast Cancer and Art-induced Contralateral Breast Cancer (Art-cbc)mentioning
confidence: 96%
“…Correcting the DNA mismatch progress [19] Cell cycle regulation genes TP53 Forming a homotetramer binding to TP53 response elements in DNA [21] PTEN Inhibiting of the DNA proliferation at the G1-S transition [24] DNAH11 Activating of p38 mitogen-activated protein kinase (MAPK) pathway [28] CDKN2A/B Inhibiting of the DNA proliferation at the G1-S transition [30] MICA Modulation in immune response regulation for cell cycles [31] Cell-to-cell adhesion genes CDH1 Coding E-cadherin adhesion protein [32] Metabolism genes PON1 Coding a multifactorial antioxidant enzyme [35] ABC Encoding large membrane proteins relating the energy dependent transport of xenobiotics [38] 3 Breast cancer susceptibility genes [10] . Two cohort studies by Engel and Fischer [11] indicated that the cumulative risk of first-time breast cancer at age 60 was 61.8% for BRCA1 mutation carriers, 43.2% for BRCA2 mutation carriers and 15.7% for non-carriers. Simultaneously, compared to that of normal people, breast cancers with BRAC1 mutations tended to be diagnosed at an earlier age and were more likely to be estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) negative [12].…”
Section: Mlh1 /Msh2mentioning
confidence: 99%